Evaluating a community-based cervical cancer screening strategy in Western Kenya: a descriptive study - Megan Swanson; Saduma Ibrahim; Cinthia Blat; Sandra Oketch; Easter Olwanda; May Maloba; Megan J Huchko (BMC Women's Health, 2018)
Abstract Background The incidence of cervical cancer in Kenya is among the highest in the world. Few Kenyan women are able to access screening, thus fueling the high cervical cancer burden. Self-collected human papilloma Virus (HPV) tests, administered during community-health campaigns in rural areas may be a way to expand access to screening. Methods In December 2015, we carried out a four-day community health campaign (CHC) to educate participants about cervical cancer prevention and offer self-administered HPV screening. Community enumeration, outreach and mobilization preceded the CHC. Samples were sent to Migori County Hospital for HPV DNA testing using careHPV Test Kits. Women were notified of results through their choice of short message service (SMS), phone call, home visit or clinic visit. HPV positive women were referred for cryotherapy following a screen-and-treat strategy. Results Door-to-door enumeration identified approximately 870 eligible women in Ngodhe Community in Migori County. Among the 267 women attending the campaign, 255 women enrolled and collected samples: 243 tests were successfully resulted and 12 were indeterminate. Of the 243 resulted tests, 47 (19%) were positive for HPV, with young age being the only significant predictor of positivity. In multivariate analysis, each additional year of age conferred about a 4% decrease in the odds of testing positive (95% CI 0.1 to 7%, p = 0.046). Just over three-quarters of all women (195/255), were notified of their results. Those who were unable to be reached were more likely to prefer receiving results from clinic (54/60, 90%) and were less likely to have mobile phones (24/60, 73%). Although 76% of HPV positive women were notified of their results, just half (51%) of those testing positive presented for treatment. HPV positive women who successfully accessed the treatment facility did not differ from their non-presenting counterparts by demographics, health history, desired route of notification or access to a mobile phone. Conclusion Nearly a third of eligible women in Ngodhe Community attended the CHC and were screened for cervical cancer. Nearly all women who attended the CHC underwent cervical cancer screening by self-collected HPV tests. Three-quarters of all participants received results, but just half of HPV positive participants presented for treatment in a timely fashion, suggesting that linkage to treatment remains a major challenge. Trial registration NCT02124252, Registered 25 April 2014.